Extend of unhealthy behaviours of patients with cardiovascular diseases during the second COVID-19 lockdown in Northern Greece: comparison between urban and rural residents. (11th May 2022) - Ioannidis, A; Fragkiskou, A; Pechlevanis, A; Paraskelidou, M; Giakoumi, V; Asmani, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Unhealthy behaviours can be amplified during lockdown and organisations, like WHO and CDC, campaign on how to stay healthy at home. Lifestyle choices are of paramount importance for primary and secondary prevention of cardiovascular diseases (CVDs). Northern Greece was forcefully hit by the second wave of the COVID-19 pandemic and a hard lockdown was implemented in November 2020. Purpose: The aim of the study was to assess the (un)healthy behaviours of patients with CVDs during the second COVID-19 lockdown in Northern Greece and to compare the urban with the rural population. Methods: This is a cross-sectional short questionnaire telephone-based survey conducted in February 2021. Responders with known CVDs were primarily questioned (using a Likert-like scale) about smoking, diet and physical activity, along essential medical history. Beliefs about COVID-19 pandemic and vaccination were also considered. Sociodemographic details were noted. Patients who were placed under quarantine were excluded in this analysis. Results: The response rate was high (438 out of 700 calls, 62.6%) with the majority of the participants willing to speak for longer time than initially estimated. In total, answers by 395 patients (216 urban and 179 rural) (female 252/63.8%, mean age 57.3 years old) were incorporated. There were 200 active smokers questioned (urban: 119, 55.1% - rural: 81, 45.3%). More urban residents increased smoking (56, 47.1%) than rural ones (24, 29.6%). Of note, the majority of the rural patients reported smoking similarly than before the lockdown. Unfortunately, none of the questioned participants attempted to quit smoking. The mean BMI of the urban patients was 27.5 ± 4.3 kg/m² (vs. 26.8 ± 3.8 kg/m² before lockdown) corresponding to a mean weight gain of about 2 kg. The rise in mean BMI could be explained, partly, by the increased eating as reported by almost half of the urban participants (121, 56.0%). There was a smaller increase in mean BMI of the rural sample (from 26.6 ± 3.9 kg/m² to 26.9 ± 4.1 kg/m²) corresponding to a mean weight gain of less than 1 kg. The limited weight gain is represented by the majority of the rural patients reported that they didn't change their eating habits. The vast minority of the urban and the rural participants answered that they increased exercising in comparison to their pre-lockdown habits (39, 18.1% vs 37, 19.4%, p>0.05), Contrary to that, more than half of the rural patients had maintained similar levels of physical activity (109, 57.1%). Conclusion: The hard lockdown in Greece during the second wave of the COVID-19 pandemic was accompanied with an aggravation of unhealthy choices by patients with CVDs. This observation was more apparent in the urban population. Further research is warrant to assess the clinical impact of these behaviours. Public campaigns are anxiously needed to promote healthy behaviours.